Internal audit in the federal government ministries, departments and agencies of Malaysia - Md Ali, Azham (Universiti Utara Malaysia, 2007)
The internal audit function is around to help members of organization in improving their activities.But the findings from in‐depth interviews conducted in the middle of 2004 with internal auditors from a total of 40 federal government ministries, departments and agencies in Malaysia have revealed a number of serious shortcomings that far outweigh the few virtues around.That is, many internal audit units have to face with the problem of shortage of staff and audit staff lacking in competency in internal audit.In addition, a majority of the audit units which are mostly operating in the less than advance audit mode has failed to get the right level of support and assistance from the Treasury and other parties.Worse, their effectiveness and efficiency is threatened by the high‐handed conduct of the National Audit Department over the shifting of its cadre staff in and out of the internal audit units.Despite all these problems, the internal auditors are quite optimistic of the audit future.On the other hand, politics of accountability theory, power distance and a Malaysian social context that replete with cases of the lack of transparency and public accountability of its major actors point to the audit’s probable bleak future.